TOBACCO RELATED CONTENT ON NEW MEDIA AND ITS EXPOSURE AMONG UNIVERSITY STUDENTS IN BANGLADESH - Uddin, Md. Jahir; Islam, Md. Azizul; Asad, Md. Asaduzzaman Mondol (American International Journal of Social Science Research, 2021)
The study investigates the tobacco-related content on new media and its exposure among university students in Bangladesh. A cross-sectional study design based on mixed-method approach had been used to conduct this study. A sample of 405 respondents were selected from eight public universities in Bangladesh for the survey questionnaire. Besides, 20 key informant interviews were conducted with structured question, and a checklist used for new media observation regarding tobacco-related contents. Quantitative analysis performed with descriptive and inferential statistics for survey data, while thematic analysis followed for qualitative data. The study revealed that 43.5% of respondents were exposed to tobacco-related content (TRC) in New Media. Regarding exposure to TRC, Facebook (43.5%) was on the top, followed by YouTube (39.2%), Instagram (35.6%), Online Newspaper (25.2%), Blog (22.2%) and Twitter (12.5%). Study shows that one-fifth of the respondents (20.2%) had an engagement with these TRC by post, share, like and comment through Facebook, YouTube, and Twitter. KII explored that TI promotes their products using names and logos, violating the TAPS ban, which was shared by new media users and exposed to university students. Finally, the study concludes that for attracting the university students, the tobacco industry has developed different tools and techniques in new media.